2018
DOI: 10.1021/acsami.7b17662
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Control in the in Situ Synthesis of Iconic Metal–Organic Frameworks within an Ionic Polymer Matrix

Abstract: Ionic polymers that possess ion-exchangeable sites have been shown to be a greatly useful platform to fabricate mixed matrices (MMs) where metal-organic frameworks (MOFs) can be in situ synthesized, although the in situ synthesis of MOF has been rarely studied. In this study, alginate (ALG), an anionic green polymer that possesses metal-ion-exchangeable sites, is employed as a platform of MMs for the in situ synthesis of iconic MOFs, HKUST-1, and MOF-74(Zn). We demonstrate for the first time that the sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…As a typical product through in situ synthesis shown in Figure , the HKUST‐1 mixed matrices show size selectivity to separate MB from rhodamine 6G, thus this material was applied to synthesize a selective membrane by adding poly(vinyl alcohol). At present, this strategy has been proved adoptable and efficient in MOF‐74 and HKUST‐1 and has a potential to be appropriate for other MOFs …”
Section: Application Of the Hkust‐1 And Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical product through in situ synthesis shown in Figure , the HKUST‐1 mixed matrices show size selectivity to separate MB from rhodamine 6G, thus this material was applied to synthesize a selective membrane by adding poly(vinyl alcohol). At present, this strategy has been proved adoptable and efficient in MOF‐74 and HKUST‐1 and has a potential to be appropriate for other MOFs …”
Section: Application Of the Hkust‐1 And Its Derivativesmentioning
confidence: 99%
“…In situ synthesis of HKUST‐1 in alginate polymer matrix via two routes with different adding orders: route A showed ligand‐diffusional and route B showed metal ion‐diffusional. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Application Of the Hkust‐1 And Its Derivativesmentioning
confidence: 99%
“…In situ growth approach involves the growth of MOF crystals via solvothermal/hydrothermal reactions of the metal salts and ligands in the presence of another material. During the synthesis, the second material generally serves as a structure directing agent, leading to oriented growth of MOF crystals [77,78]. Hybrid materials obtained by in situ growth approach usually have ordered morphology and/or hierarchical structure, which are useful features for applications such as gas storage and small molecule separations [17,[79][80][81].…”
Section: In Situ Growthmentioning
confidence: 99%
“…As a unique framework material, metal-organic frameworks (MOFs) have a wide range of applications due to their high porosity, adjustable structure, high chemical stability, and good biocompatibility (such as adsorption, separation, catalysis, electricity chemistry, biomedicine). [10][11][12][13][14][15][16][17] Recent studies have shown that some MOFs also have good anti-bacterial properties 18,19 and good medical value, [20][21][22] including the classic zeolite imidazolate skeleton (ZIF-8), which can respond to decomposition and release Zn(II) in the acidic environment of bacterial infection. As a bactericidal factor, Zn(II) can damage cell membranes and cause cell death.…”
Section: Introductionmentioning
confidence: 99%